Effect of conjugative transfer of antibiotic resistance genes mediated by plasmids on the microecology of different intestinal segments - Ding, Chengshi; Yan, Li; Zhang, Kai; Liu, Xiangxiang; Liu, Ziyu; Hou, Shaowei; Ma, Jing; Wu, Zhiping; Wei, Hongfei (Frontiers in Microbiology, 2024)
IntroductionThe conjugative transfer of antibiotic resistance genes (ARGs) mediated by plasmids occurred in different intestinal segments of mice was explored.MethodsThe location of ARG donor bacteria and ARGs was investigated by qPCR, flow cytometry, and small animal imaging. The resistant microbiota was analyzed by 16S rRNA gene amplification sequencing.ResultsThe small intestine was the main site for the location of ARG donor bacteria and ARGs. The intestinal microbiota richness of the small intestine (duodenum and jejunum) and the large intestine (cecum, colon, and rectum) increased, and the ileum microbiota richness decreased under the action of donor bacteria. The differences in the number of bacteria in the small intestine and the large intestine, as well as the relative richness of Firmicutes from the small intestine to the large intestine, decreased. By contrast, the relative abundance of Proteobacteria increased. The intake of resistant plasmids alleviated the impact of antibiotics on intestinal microbiota, particularly increasing the proportion of Proteobacteria and Bacteroides, which were presumed to be susceptible to ARGs.DiscussionThe acquisition of ARGs by intestinal microbes is an important reason why infectious diseases are difficult to cure, which brings risks to human health and intestinal microecology.